2018
DOI: 10.1002/ejlt.201700290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Olive Pomace in the Production of Novel Broilers With Enhanced In Vitro Antithrombotic Properties

Abstract: Several attempts have been made not only to improve nutritional value of broilers but also to attenuate dependence on raw materials such as corn in compounded broilers feed. Therefore the aim of this study is to evaluate the impact of diets enriched with olive pomace (OP) on Ross 308 broilers growth performance, sensory characteristics, and nutritional value in terms of cardioprotection. Broilers are fed four experimental diets containing 0% OP (control group), 2.5% OP (group A), 5.0% OP (group B), and 7.5% OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
(35 reference statements)
0
8
0
Order By: Relevance
“… PO enhanced the meat quality of broiler and could be used in the production of functional broilers meat. Nasopoulou et al (2018) Olive pomace extract (750 ppm in drinking water) No substantial changes in feed intake were observed among dietary treatments. A significant decrease in IL-8 gene and upregulated TGF-β4, and Bu-1 were noticed in broiler fed olive pomace extract.…”
Section: Effects On Meat Qualitymentioning
confidence: 96%
See 1 more Smart Citation
“… PO enhanced the meat quality of broiler and could be used in the production of functional broilers meat. Nasopoulou et al (2018) Olive pomace extract (750 ppm in drinking water) No substantial changes in feed intake were observed among dietary treatments. A significant decrease in IL-8 gene and upregulated TGF-β4, and Bu-1 were noticed in broiler fed olive pomace extract.…”
Section: Effects On Meat Qualitymentioning
confidence: 96%
“…Trails suggested that the dietary levels of NSP could affect the health or performance of the broiler ( Zahi et al, 2022 ). For the chemical composition of olive pomace ( Nasopoulou et al, 2018 ), the fat, protein, fiber, total carbohydrates and organic matter were 18.3, 9.8, 21.5, 58.9, and 92.9%, respectively ( Table 1 ). Olive pomace extract or oils also have bioactive compounds such as total triterpenes (oleanoic and maslinic acids) and polyphenols in olive pomace oils ( Mateos et al, 2020 ).…”
Section: Chemical Components Of Olive Oil and Its Derivativesmentioning
confidence: 99%
“…Higher levels of OC (82.5-165 g/kg diet) seemed to enhance daily weight gain, meat antioxidant status, and oxidative stability [138]. The inclusion of 5% olive pomace in broiler diets also improved breast and thigh sensory attributes and antithrombotic properties [139].…”
Section: Olive Oil Industry By-productsmentioning
confidence: 99%
“…A variety of wastes and byproducts are produced during the olive oil processing process. The main ones with significant nutritional and technological interests are olive pomace, olive mill waste waters, olive leaves, and olive stone and seed ( Nasopoulou and Zabetakis 2013 ; Nunes et al, 2016 ; Nasopoulou et al, 2018 ). In this review, we reviewed existing information of olive oil and derivatives positive health uses and prospective effects on poultry production in this review ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%